A Study Of Coupled Magnetic Fields For An Optimum Torque Generation - Mohd Suhadis, Nurulasikin; Varatharajoo, Renuganth (2011)
Magnetic torquers are specifically designed to generate a magnetic field onboard the satellites for their attitude control. A control torque is generated when the magnetic fields generated by the magnetic torquers couple with the geomagnetic fields, whereby the vector of the generated torque is perpendicular to both the magnetic fields.